Feelings : a little book of emotions - Pat-a-Cake; Karabatzia, Villie (London Pat-a-Cake, 2020)
Help toddlers discover and learn about themselves and the world with these essential board books. Feelings helps busy, curious toddlers explore their world and develop their vocabulary by lots of words about feelings. It is important to encourage children to talk about feelings and understand why they have them. This book will equip them with the vocabulary to do so. This robust board book will withstand many happy hours of looking, holding, exploring and reading, while the playful, witty illustrations will be loved by parents and children alike. A brilliant fold-out surprise at the end adds a fun recap of all the learning in the book
Linguistic Notions
Keywords: Children's stories; Fiction